Variants of MicroRNA Genes: Gender-Specific Associations with Multiple Sclerosis Risk and Severity - Kiselev, Ivan (Int J Mol Sci, 2015)
Multiple sclerosis (MS) is an autoimmune neuro-inflammatory disease arising from complex interactions of genetic, epigenetic, and environmental factors. Variations in genes of some microRNAs—key post-transcriptional regulators of many genes—can influence microRNAs expression/function and contribute to MS via expression changes of protein-coding target mRNA genes. We performed an association study of polymorphous variants of MIR146A rs2910164, MIR196A2 rs11614913, MIR499A rs3746444 MIR223 rs1044165 and their combinations with MS risk and severity. 561 unrelated patients with bout-onset MS and 441 healthy volunteers were enrolled in the study. We observed associations of MS risk with allele MIR223*T and combination (MIR223*T + MIR146A*G/G) carriage in the entire groups and in women at Bonferroni-corrected significance level (p(corr) < 0.05). Besides, MIR146A*G/G association with MS was observed in women with nominal significance (p(f) = 0.025). No MS associations were found in men. A more severe MS course (MSSS value > 3.5) was associated with the carriage of MIR499A*C/T and, less reliably, of MIR499A*C (p(corr) = 0.006 and p(corr) = 0.024, respectively) and with the carriage of combinations (MIR499A*C/T + MIR196A2*C) and (MIR499A*C + MIR196A2*C) (p(corr) = 0.00078 and p(corr) = 0.0059, respectively). These associations also showed gender specificity, as they were not significant in men and substantially reinforced in women. The strongest association with MS severity was observed in women for combination (MIR499A*C/T + MIR196A2*C): p(corr) = 4.43 × 10(−6) and OR = 3.23 (CI: 1.99–5.26).